2020
DOI: 10.1155/2020/2529730
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effects of Alkaloids from the Bulbs of Crinum abyscinicum Hochst. ExA. Rich

Abstract: Crinum abyscinicum Hochst. ExA. Rich bulb is traditionally used in Ethiopia for the treatment of various ailments including internal parasites, mastitis, rabies, colic diseases of animals, and cancer. Despite its importance in traditional cancer treatment, no research work has been reported on the antiproliferative activity of the bulb extract and its major constituents. Phytochemical investigation of the bulb extract of C. abyscinicum by PTLC over silica gel resulted in the isolation of two alkaloids, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Additionally, several alkaloids contained in the extracts have been previously identified to have anticancer activity. Lycorine showed significant antiproliferative effects against A2780 and MV4-11 cells [46]. Previous studies have demonstrated that lycorine and haemanthamine were able to inhibit cell proliferation using a panel of 16 tumor cell lines [5].…”
Section: Antiproliferative Effectsmentioning
confidence: 92%
“…Additionally, several alkaloids contained in the extracts have been previously identified to have anticancer activity. Lycorine showed significant antiproliferative effects against A2780 and MV4-11 cells [46]. Previous studies have demonstrated that lycorine and haemanthamine were able to inhibit cell proliferation using a panel of 16 tumor cell lines [5].…”
Section: Antiproliferative Effectsmentioning
confidence: 92%
“…Crinum species are extremely rich in alkaloids. Many alkaloids isolated from these plants demonstrated anticancer activity in several in vitro studies [15].…”
Section: Introductionmentioning
confidence: 99%